Improving Community Competence in Web Development through Company Profile Website Training - Richard, Chlyfen; Ningrum, Via; Ramadhan, As'ary (Digital Innovation, 2025)
The development of information technology requires society to acquire skills in web development, particularly in creating company profile websites that serve as essential media for information and company promotion. The partners of this program still face limitations in understanding website design, including database, backend, and frontend aspects. The solution provided was intensive online training aimed at improving participants’ knowledge and practical skills. The methods applied consisted of interactive lectures, hands-on practice, and discussion sessions. The results showed an improvement in participants’ abilities to design and implement company profile websites in line with current digital needs. The outcomes of this program include learning modules, e-certificates, and online documentation, which are expected to contribute to enhancing community competence in information technology, especially in web development.